SP0023 How to Measure Physical Activity in People with Rheumatoid Arthritis. (9th June 2015) - Larkin, L.
Abstract : Physical activity is recognized globally as a key factor in health (1). Measurement of both physical activity and sedentary behavior patterns is complex and can be conducted using subjective or objective methods. Subjective methods of measurement are reported to be less accurate than objective methods (2). Objective, wearable activity monitors are now widely used in research studies and work by using physiological or mechanical responses to bodily movement as signals to estimate variables that reflect physical activity (3). This session will examine the measurement of physical activity behaviour in people with rheumatoid arthritis (RA). The focus will be on objective measures which have been validated in the people with RA to date. Initially the session will provide an introduction to the measurement of physical activity and key aspects of measurement. A review of studies measuring physical activity in RA will then be provided with consideration of the applicability of these studies in a clinical setting. Finally, the session will identify future opportunities for research and will consider how physical activity can be measured in everyday situations. References: Haskell, WL, Lee, IM, Pate, RR, Powell, KE, Blair, SN, Franklin, BA, Macera, CA, Heath, GW, Thompson, PD, Bauman, A. (2007). Physical activity and public health: updated recommendation for adults from the American College of Sports Medicine and the American Heart Association. Med Sci Sports Exerc 39:1423–34 Warren, MJ, Ekelund, U, Besson, H, Mezzani, A, Geladas, N, Vanhees, L. (2010). Assessment of physical activity - a review of methodologies with reference to epidemiological research: a report of the exercise physiology section of the European Association of Cardiovascular Prevention and Rehabilitation. European J of Cardiovasc Prev and Rehabil 17(2):127-39 Bassett DR, Rowlands AV, Tost SG. (2012). Calibration and Validation of Wearable Monitors. Med Sci Sports Exerc 44(1 Suppl 1):S32–S38 Disclosure of Interest: None declared